EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH DALAM MENGEMBANGKAN BUDAYA LITERASI - Azizah, Alif Luthvi; Latief, Abdul Majid; Tumanggung, Anen (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2018)
This research aims to find out how far the Effectiveness of School Principal?s Leadership in Developing Culture of Literacy at Aziziyyah Islamic High School, Tangerang. The methods used is qualitative approach.The results of this study indicate that the design of literacy culture development in MA Aziziyyah Tangerang has been adapted to the GLS guidelines formulated by the Ministry of Education and Culture. Includes stages: Habituation Stages, Development Stages, and Learning Stages. Indicators of achievement in these stages were met with 30 items out of a total of 37 items. These results indicate that each stage in the design of literacy culture development runs optimally in accordance with the objectives to be achieved. Several factors influence the development of literacy culture in MA Aziziyyah Tangerang, including: psychosocial factors, leadership factors, environmental factors, organizational factors, ecological factors, and government policies. These factors tend to have a positive impact on the process of developing literacy culture in MA Aziziyyah. The effectiveness of the principal's leadership is the main foundation for optimizing the development of literacy culture. Indicators of achievement related to the effectiveness of MA Aziziyyah school principal leadership in developing a literacy culture fulfilled 6 items out of a total of 7 items. The results showed that the leadership carried out by the principal was quite effective.